Urgency Using The RUP Method in Developing Information System Disdukcpil Services, Subang District - Jaja (Jurnal Mantik, 2021)
The information system is defined as the process of delivering messages to one another, Disdukcapil of Subang district has problems in delivering messages, this study sees the urgency of development This research uses the RUP (Rational Unified Process) development method used when identifying a running system and describing the design. the system to be built with the aim of getting a system that is right for BPSB. The development analysis uses the RUP (Rational Unified Process) method as a tool in order to model the required business processes (business modeling) and define the system requirements to be created. In addition, this study uses the UML (Unified Modeling Language) tool. This study uses a case study as a method for data collection and retrieval where the research process begins by identifying a case to find a solution in the form of system development. Based on the results of the analysis, the running system still uses conventional methods, which results in the process of delivering information to consumers not optimal. Therefore, it is urgent to use the RUP method at Disdukcapil to make it easier for the public to control reports, KTP status and to be able to display data so that information delivery can run optimally. which resulted in the process of delivering information to consumers not optimal. Therefore, it is urgent to use the RUP method at Disdukcapil to make it easier for the public to control reports, KTP status and to be able to display data so that information delivery can run optimally. which resulted in the process of delivering information to consumers not optimal. Therefore, it is urgent to use the RUP method at Disdukcapil to make it easier for the public to control reports, KTP status and to be able to display data so that information delivery can run optimally.